Peningkatan Kinerja Penyelenggaraan Pemerintahan Melalui Difusi Inovasi Daerah - Biryanto (Jurnal Kebijakan Pembangunan dan Inovasi, 2019)
The diffusion of regional innovation is the activity of disseminating information about regional innovations carried out by local governments to the community. An important objective of regional innovation is to improve the performance of regional government administration, which has the effect of accelerating the realization of people's welfare. The method used in this paper is a literature review that includes communication theories, diffusion of innovation, and legislation. Based on the discussion it can be formulated that regional innovation as a message material in the communication process can be adopted quickly and broadly if its development is based on four factors namely: local government authority, community needs, development of science and technology, and legislation. The implementation of the diffusion of regional innovation effectively will encourage an increase in the performance of government administration which includes improving macro performance, the performance of regional government affairs, and accountability of local government performance.